Augmented Reality for Topeng Malangan Face Recognition as a Media for Cultural Education - Setiabudi Sakaria; Aldino Wildhan Kurniawan (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
Topeng Malangan is one of Malang's original culture that needs to be preserved. However, the survey results show that 65.9% of respondents are not familiar with Topeng Malangan. Currently Topeng Malangan is less popular among the people of Malang city, because Topeng Malangan art is rarely performed and only a little introduced through dance learning in elementary schools. There are 76 Topeng Malangan figures with six famous figures, namely Raden Gunung Sari, Dewi Sekartaji, Dewi Ragil Kuning, Bapang, Panji Asmoro Bangun, and Klono Sewandono. This research produces face recognition software through Augmented Reality using a marker tracking model. Two-dimensional marker as the printed or the cellphone screen displayed figures, will be performed as a three-dimensional image of the mask face. In addition to three-dimensional images, figuring character information, text and sound are also showed according to the characteristics of the Topeng Malangan from Desa Kemantren Kecamatan Jabung, Kabupaten Malang, Jawa Timur. The blackbox testing of the application shows that all application parameters are functioning properly. This application can be used as a learning medium in the form of educational games about Topeng Malangan figures and culture